2008
DOI: 10.1117/12.810602
|View full text |Cite
|
Sign up to set email alerts
|

Wireless telemetry system for a SAW based microvalve

Abstract: Inductively coupled RF telemetry is an optimal method for both power supply and data transmission in long term artificial implants due to small size, high reliability, and extended life span of the device. In this research, we propose the use of the same technique for secure remote interrogation and powering of a human implantable, Surface Acoustic Wave (SAW) correlation based, passive microvalve. This is carried out by interrogating the microvalve with a Barker sequence encoded BPSK signal. In this paper we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The valve was designed to be driven by the minimum value about electromagnetic (EM) radiation, considering existing EM radiation. Length about the required code was researched to guarantee safe manipulation [122,123,125,126]. Zhang et al reported a novel SAW microvalve consisted of the piezoelectric substrate and an interdigital transducer (27.5 MHz).…”
Section: Metal Phase Transition Actuation Low Melting Point Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…The valve was designed to be driven by the minimum value about electromagnetic (EM) radiation, considering existing EM radiation. Length about the required code was researched to guarantee safe manipulation [122,123,125,126]. Zhang et al reported a novel SAW microvalve consisted of the piezoelectric substrate and an interdigital transducer (27.5 MHz).…”
Section: Metal Phase Transition Actuation Low Melting Point Alloymentioning
confidence: 99%
“…Many microvalves based on SAW are utilized to for the purpose of secure wireless actuation. There are lots of advantages in the realization of a SAW microvalve including secure [122], reliable and low power operation [121], small size [123], simplicity in construction [124] and cost effectiveness [125]. Such microvalves have a huge range of applications such as in micro electro-mechanical systems (MEMS), nano electro-mechanical systems (NEMS) [121], biomedical applications, lab-on-chip applications [124], drug delivery [125,126], and so on.…”
Section: Metal Phase Transition Actuation Low Melting Point Alloymentioning
confidence: 99%